2015
DOI: 10.1097/md.0000000000001502
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of Superb Microvascular Imaging (SMI) in Detecting Blood Flow Signals of Breast Lesions

Abstract: The correlation between color Doppler flow imaging (CDFI) and Superb Microvascular Imaging (SMI) for detecting blood flow in breast lesions was investigated, as was the diagnostic value of SMI in differentiating benign from malignant breast lesions.These lesions were evaluated using both CDFI and SMI according to Adler's method. Pathologic examination showed 57 malignant lesions and 66 benign lesions. The number of blood vessels in a single mass was detected by 2 techniques (SMI and CDFI), and the difference b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
155
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(164 citation statements)
references
References 24 publications
6
155
0
3
Order By: Relevance
“…Furthermore, SMI revealed more details of microvasculature, such as tiny branches and the distal part of microvessels. Therefore, our findings extended SMI's previous applications in thyroid and breast masses (Ma et al 2015;Machado et al 2016;Zhan et al 2016). The advantages of SMI are due largely to its ability to separate low-speed flow signals from motion artifacts.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Furthermore, SMI revealed more details of microvasculature, such as tiny branches and the distal part of microvessels. Therefore, our findings extended SMI's previous applications in thyroid and breast masses (Ma et al 2015;Machado et al 2016;Zhan et al 2016). The advantages of SMI are due largely to its ability to separate low-speed flow signals from motion artifacts.…”
Section: Discussionsupporting
confidence: 66%
“…SMI accurately depicts low-speed flow signals in thyroid lesions (Machado et al 2016) and matches contrastenhanced computer tomography in the diagnosis of focal nodular hyperplasia (Wu et al 2015). Its preliminary application in breast cancer further suggested its diagnostic value (Ma et al 2015;Zhan et al 2016). Compared with conventional CDI, SMI reportedly detects more blood flow in breast lesions (Ma et al 2015).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recent technological advances in Doppler sonography (microvascular sonography) enable visualization of very low‐velocity blood flows that are typically removed on conventional color or power Doppler images without substantial motion artifacts . Recent studies highlighted the usefulness of microvascular sonography in differentiating malignant from benign lesions in the breast and in differentiating among various hepatic tumors . In our previous study, we found that a vascular pattern analysis of microvessels in cervical lymph nodes with microvascular sonography helped in differentiating between metastatic lymphadenopathy and tuberculous lymphadenitis compared with conventional power Doppler sonography …”
Section: Discussionmentioning
confidence: 92%
“…Some recent reports have also noted that SMI is useful for assessing minute vascular flow in patients with carpal tunnel syndrome [10] and breast lesions [11]. SMI is also useful for visualizing the small vascular architecture of the liver surface associated with progression of fibrosis in patients with chronic hepatitis C [12].…”
Section: Fhcs Was Initially Reported By Curtis Et Al In Open Surgerymentioning
confidence: 99%